No gender difference in confidence or metacognitive ability in perceptual decision-making - Kai Xue; Yunxuan Zheng; Christina Papalexandrou; Kelly Hoogervorst; Micah Allen; Dobromir Rahnev (iScience)
Summary: Prior research has found inconsistent results regarding gender differences in confidence and metacognitive ability. Different studies have shown that men are either more or less confident and have either higher or lower metacognitive abilities than women. However, this research has generally not used well-controlled tasks or used performance-independent measures of metacognitive ability. Here, we test for gender differences in performance, confidence, and metacognitive ability using data from 10 studies from the Confidence Database (total N = 1,887, total number of trials = 633,168). We find an absence of strong gender differences in performance and no gender differences in either confidence or metacognitive ability. These results were further confirmed by meta-analyses of the 10 datasets. These findings show that it is unlikely that gender has a strong effect on metacognitive evaluation in low-level perceptual decision-making and suggest that previously observed gender differences in confidence and metacognition are likely domain-specific.